The TESOL Encyclopedia of English Language Teaching 2018
DOI: 10.1002/9781118784235.eelt0034
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Qualifications, Professionalism, Competencies, and Benchmarks

Abstract: To achieve professionalism, English language teachers (both native English‐speaking teachers [NESTs] and non‐native English‐speaking teachers [NNESTs]) need to gain competence in disciplinary content knowledge about the nature of language, language learning, and language teaching, as well as pedagogical content knowledge regarding teaching strategies that they can use to make their teaching contextually appropriate and effective. Teachers also need to achieve the ability to use English effectively for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Studies have shown that mentoring and induction programmes have been an important aspect of teacher education in many countries worldwide, particularly since the 1980s (Gjedia & Gardinier, 2018). Mentoring has been found to increase teacher retention (Doğançay-Aktuna & Hardman, 2018), improve new teacher job satisfaction and self-efficacy (Ingersoll & Strong, 2011), enhance teachers' pedagogical content knowledge (Spooner-Lane, 2017), reduce new teachers' feelings of isolation (Mamlok-Naaman & Eilks, 2012) and promote teachers' ongoing professional development and lifelong learning (Snoek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mentoring and induction programmes have been an important aspect of teacher education in many countries worldwide, particularly since the 1980s (Gjedia & Gardinier, 2018). Mentoring has been found to increase teacher retention (Doğançay-Aktuna & Hardman, 2018), improve new teacher job satisfaction and self-efficacy (Ingersoll & Strong, 2011), enhance teachers' pedagogical content knowledge (Spooner-Lane, 2017), reduce new teachers' feelings of isolation (Mamlok-Naaman & Eilks, 2012) and promote teachers' ongoing professional development and lifelong learning (Snoek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge base underpins professional action, but professionalism is beyond knowledge acquisition (Moore, 2017). Professionalism requires continual knowledge update through research utilisation (Doğançay-Aktuna, & Hardman, 2018). Though the process of knowledge acquisition is the primary stage of professionalism.…”
Section: Introductionmentioning
confidence: 99%
“…Though the process of knowledge acquisition is the primary stage of professionalism. However, before an individual can be regarded as a professional, there are regulated knowledge pathways through structured institution under which the person must study (Doğançay-Aktuna & Hardman, 2018;Moore, 2017). Learning and registration make an individual become a registered professional, but beyond registration, an individual requires knowledge update through engagement in research enquiry and utilising of findings from research (Moore, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in research in English as an International Language (EIL), World Englishes (WE) and English as a Lingua Franca (ELF) demands a paradigm shift in English Language Teaching (ELT) among scholars. Furthermore, the successful implementation of any changes in ELT requires and depends on successful innovations in teacher preparation (Dogancay–Aktuna & Hardman, 2008; Matsuda, 2006). Aya Matsuda intelligently brings together this volume under review which comprises six parts, including 15 chapters, examining theoretical frameworks, programs, courses and units, model lessons, activities and tasks for ELT teacher education from the perspective of EIL with the purpose of offering approaches to preparing in-service and pre-service teachers to meet the diverse needs of English learners today.…”
mentioning
confidence: 99%
“…Arktuna and Hardman (p. 19) outline a complementary framework by integrating an EIL perspective into Teaching English to Speakers of Other Languages (TESOL) teacher education and discuss specific topics, practical activities and pedagogical resources. They define EIL as a ‘paradigm for thinking, research and practice’ (Dogancay-Aktuna & Hardman, 2008) in applied linguistics, emphasizing the international and intercultural nature of English, and present their EIL teacher education model as an interaction between place, proficiency, praxis and a set of understandings about language, culture, and identity teaching related to EIL pedagogy.…”
mentioning
confidence: 99%